ANTIBIOFILM ACTIVITY OF MANGOSTEEN (Garcinia mangostana L.) LEAF EXTRACT AGAINST COLLECTION OF BACTERIAL ISOLATES FROM DIABETIC ULCERS - Gubali, Derina Dwifrila Ridhani; Rasdianah, Nur; Akuba, Juliyanty; Abdulkadir, Widy Susanti; Uno, Wiwit Zuriati (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2024)
Mangosteen (Garcinia mangostana L.) is a plant that contains many benefits and has the potential to be a medicinal plant in treating various diseases. Mangosteen leaves contain flavonoids, saponins, tannins, alkaloids and terpenoids which are known to have antibacterial and antibiofilm properties. This anti-biofilm agent is an alternative treatment for diabetic wound infections where cases of antibiotic resistance have increased. One of the causes of resistance is the biofilm formed by infectious bacteria. This research is a type of laboratory experimental research which aims to determine the anti-biofilm activity of mangosteen leaf extract against biofilms formed by a collection of bacterial isolates from diabetic wounds. The antibiofilm activity test carried out consisted of a cell attachment prevention test, a biofilm formation inhibition test, and a biofilm destruction test using the crystal violet staining method using the tube method and measuring optical density values ​​on a UV-Vis spectrophotometer. The concentrations of mangosteen leaf extract used are 60%, 80% and 100% as well as control – and control +. The results of the antibiofilm test showed that mangosteen leaf extract had the best activity in inhibiting biofilm formation, preventing cell attachment, and destroying biofilm, respectively. The three most optimal activities were found at a concentration of 100%, with an inhibition percentage of 50.51%, prevention of 32.56%, and destruction of 5.63%.